Increased serum ferritin is associated with severity of orbital disease in COVID-19–associated rhino-orbito-cerebral mucormycosis: A quantitative analysis - Shashi Tanwar; Nibha Mishra; Prachi Sharma; Apjit Kaur (Indian Journal of Ophthalmology)
Context: Effect of serum ferritin on severity of coronavirus disease 2019 (COVID-19)-associated rhino-orbito-cerebral mucormycosis. Purpose: To study the association between increased serum ferritin and severity of orbital disease in COVID-19–associated rhino-orbito-cerebral mucormycosis. Settings and Design: A cross-sectional study. Methods: Hundred (n) out of 155 treatment-naive patients of COVID-19 infection presenting with the signs and symptoms of rhino-orbito-cerebral mucormycosis were enrolled in study. Based on the classification proposed by Honavar, the study patients were classified into four stages: Stage 1: involvement of the nasal mucosa (n = 11), Stage 2: involvement of paranasal sinuses (n = 14), Stage 3: involvement of the orbit (n = 37), Stage 4: involvement of the central nervous system (n = 38). Stage 3 was further divided into four substages: 3a: nasolacrimal duct, medial orbit, vision unaffected (n = 4); 3b: diffuse orbital involvement (>1 quadrant or >2 structures), vision unaffected (n = 15); 3c: central retinal artery occlusion or ophthalmic artery occlusion, superior ophthalmic vein thrombosis, involvement of superior orbital fissure, inferior orbital fissure, orbital apex, diminution or loss of vision (n = 13); 3d: bilateral orbital involvement (n = 5). Fasting blood sugar (FBS), postprandial blood sugar (PPBS), and inflammatory markers (serum ferritin, interleukin-6, C-reactive protein, and D-dimer) were assessed. Serum level of ferritin was analyzed by using chemiluminescence immunoassay method. Results: Mean FBS (mg/dl) was 165.03 ± 70.43 for stage 1, 185.67 ± 64.82 for stage 2, 159.05 ± 68.60 for stage 3, and 158.20 ± 62.05 for stage 4. Mean PPBS (mg/dl) was 238.70 ± 141.29 for stage 1, 252 ± 103.69 for stage 2, 257.09 ± 103.48 for stage 3, and 229.53 ± 76.81 for stage 4. Mean serum ferritin (μg/l) was 302.67 ± 266.95 in stage 1, 444.19 ± 116.36 in stage 2, 504.85 ± 205.99 in stage 3, and 825.95 ± 777.30 in stage 4. A statistically significant increase in serum ferritin levels with severity of disease (P = 0.005) was noted. Similar trend was observed in substages of stage 3. Pearson correlation analysis showed a positive correlation between serum ferritin and severity of disease (P = 0.0007). Conclusion: Increased serum ferritin was significantly independently associated with severity of orbital disease in COVID-19–associated rhino-orbito-cerebral mucormycosis.